(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2025)
Spinal cord injury (SCI) can lead to permanent disability in affected patients. Previous studies have indicated that mesenchymal stem cells (MSCs) hold potential as therapeutic tools for treating SCI, but the specific mechanisms underlying their effectiveness have yet to be determined. This study aimed to evaluate the functional significance of exosomes produced from bone marrow mesenchymal stem cells (BMSCs) in treating SCI, explicitly focusing on the regulatory mechanism involving miR-133b and NLRP3. SCI rats received intravenous tail-vein injections of BMSC exosomes (control or miR-133b exosomes). The spinal tissue levels of miR-133b in SCI rats were determined by qPCR. Hind-limb motor function was assessed using Basso Beattie Bresnahan (BBB) scores and Western blot was utilized for analysis of NLRP3 protein levels. Damage and regeneration of spinal neurons were assessed using Nissl, immunofluorescent staining, and immunohistochemistry. Exosomes were successfully harvested from BMSCs following miR-133b transfection, and acute improvements in SCI recovery were observed following the exosomal delivery of miR-133b, as evidenced by short-term improvements in the survival of neurons and associated functional recovery. These miR-133b-containing exosomes were also able to mitigate neuroinflammatory activity by suppressing astrocyte and microglia activation. MiR-133b, at the molecular level, can decrease the production of NLRP3 mRNA by binding to its 3’-untranslated region. As a result, it inhibits the activation of the NLRP3 inflammasome, which is a crucial factor in the neuroinflammatory activity and neuronal damage associated with SCI. The results presented here provide compelling evidence that exosomes isolated from bone marrow-derived microglia overexpressing miR-133b can, at least partially, mitigate the severity of spinal cord injury by targeting the miR-133b/NLRP3 axis in the acute phase. However, due to the short survival time of the subjects, the long-term effects remain unclear, necessitating further investigation of this treatment approach.